2022
DOI: 10.1002/hsr2.941
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal attempts and self‐poisoning: 1‐year retrospective cohort study from the quaternary hospital in Thai metropolitan area

Abstract: Background and Aims In Thailand, suicide is the leading cause of death among middle‐aged adults. We believe suicide characteristics depend on different cultural/socioeconomic status. This study aimed to describe the characteristics and associated factors of suicidal attempts by self‐poisoning in Bangkok, the metropolitan city of Thailand. Methods Records of all patients visiting the emergency department of King Chulalongkorn Memorial Hospital, Bangkok, Thailand, with se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
2
3
0
Order By: Relevance
“…Family members living together with patients might be beneficial to curb anxiety, and this could be explained that such accompany was a protective factor for anxious status. Previous study had already showed that female was vulnerable to self-poisoning suicide [ 10 , 14 ], and our study also depicted a similar trend. But, interestingly, having female family members helped to prevent self-poisoning suicide for patients.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Family members living together with patients might be beneficial to curb anxiety, and this could be explained that such accompany was a protective factor for anxious status. Previous study had already showed that female was vulnerable to self-poisoning suicide [ 10 , 14 ], and our study also depicted a similar trend. But, interestingly, having female family members helped to prevent self-poisoning suicide for patients.…”
Section: Discussionsupporting
confidence: 88%
“…Identification of risk and protective factors is a crucial component of national suicide prevention since it helps to further understand the kind and type of preventive actions needed. Risk factors can occur on a variety of scales, including the individual, sociocultural, and situational, and numerous factors have been linked to increased self-poisoning, including borderline personality disorder or traits [ 9 , 10 ], alcohol use disorder [ 9 ], depressive disorder [ 9 ], substance abuse [ 11 , 12 ], asthma [ 11 ], fewer social connections [ 13 ], living in neighborhoods [ 13 ], being female [ 10 , 14 ], and being young [ 13 ]. However, to the author’s best knowledge, there were few research that looked at the relationship between the mental health state of self-poisoning patients and their family members.…”
Section: Introductionmentioning
confidence: 99%
“…6 Therefore, this discussion is about ways to reduce ED LOS, which can reduce ED overcrowding. First of all, the average ED LOS of psychiatric emergency patients in this study was 19.5 h. These results are similar to the average of 24 h in a study 17 conducted at a tertiary hospital located in Bangkok, Thailand. However, in a study 18 conducted at Calary Hospital, Alberta, Canada, the average ED LOS was as low as 14 h. It is believed that this difference in ED LOS was partly due to the difference in the time when the study was conducted.…”
Section: Discussionsupporting
confidence: 87%
“…However, in a study 18 conducted at Calary Hospital, Alberta, Canada, the average ED LOS was as low as 14 h. It is believed that this difference in ED LOS was partly due to the difference in the time when the study was conducted. This study and the study of Thumtecho et al 17 were conducted in the context of the COVID-19 pandemic, and the study of Lane et al 18 collected data in April 2014 and March 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Suicide methods vary around the world depending on socio-cultural backgrounds and variations in national laws, which affect both the suicide rate and suicide methods [ Vijayakumar, L. 2021]. Self-poisoning, firearms, and hanging are the most commonly used [Thumtecho, S.,2022]. While the United States views it as the most popular method of suicide attempt among minors, suicidal self-poisoning accounts for about 25% of all suicides in the United Kingdom [ The term quality of life refers to the improvement in the level of material and social services provided to members of society, as well as individuals' awareness of the extent to which these services can meet their various needs (Haraldstad, K.,2019).…”
Section: Introductionmentioning
confidence: 99%